Análise da eficácia de métodos de reforço de pontes rodoviárias de concreto armado - Caroline Buratto de Lima e Oliveira (2013)
The Brazilian highway system consists largely of bridges constructed prior to 1984. These bridges are under strength with respect to todays traffic. Consequently some of them were strengthened, but their number is still statistically small compared to the total amount of existing bridges. Several methods are used for strengthening reinforced concrete bridges. The choice of method is the result of many variables, such as the analysis of the intrinsic characteristics of each bridge, the surrounding environment, and finally the cost-benefit analysis. In this scenario, the object of this dissertation is the analysis of the efficiency of the strengthening procedures executed in reinforced concrete bridges, based on inspections conducted afterwards. Four bridges were chosen for the study, which have been strengthened for at least 6 years. The collected data provide knowledge of how efficient the different strengthening procedures are. This will certainly contribute in the long term to a better selection of the strengthening procedures which in turn will extend the service life of existing bridges.